O bezpośredniości interesu prawnego w prawie administracyjnym - Jakimowicz, Wojciech (Studia Prawa Publicznego, 2022)
The aim of the article is to draw attention to the direct nature of the legal interest and to try to answer the question about the sources (grounds) of this interest. The analysis is carried out from the perspective of understanding individual interest in administrative law and focuses on the issues of qualifying legal interest, including law from the perspective of the nature of the relationship between individual interest and its normative basis, and from the perspective of the normative foundations for protecting this interest. It also refers to the issue of the axiological determinants of directness legal interest in administrative law. The analysis here justifies the conclusion that the source of legal interest in administrative law comprises substantive norms belonging to the entire system of generally applicable law, which objectify the individual interest, and only the close relationship between individual interest and the legal norm which is the source of this interest allows such interest to be defined as a legal interest. The lack of a close relationship between the individual interest and the legal norm, which is considered as the source of this interest, allows such an interest to defined, from the perspective of administrative law, only as a factual interest. The close bond that must exist between an individual interest and the legal norm on which it is based in order for such an interest to be classified as a legal interest is expressed by the characteristic defined as the directness of the legal interest. The article also presents arguments to justify the thesis that the mere need to protect a legal interest, or even real protection provided to a legal interest in the area of civil law, does not constitute a source of legal interest in the area of administrative law. Just as the source of the legal interest should be sought in the norms of generally applicable law, the legislator decides on the protection and the degree of protection for this interest by establishing appropriate separate legal norms in this respect.